Theoretical aspects of emergence and development of the crisis phenomena in economy Теоретические аспекты возникновения и развития кризисных явлений в экономике - Khaustova Viktoriya Ye.; Pronoza Pavel V. (Problemi Ekonomiki, 2011)
The article examines genesis of emergence and development of the crisis phenomena in economy of the countries of the world and their research in works of scientists. The main theories explaining the reasons of cyclic crises and chronology of change of views of scientists on recurrence in development of social and economic systems are considered. The essence of the concepts “crisis” and “economic crisis” is defined. Crisis functions in dynamics of development of systems and a crisis stage are considered. As crisis is one of stages of a business cycle, phases of such cycle in economy and main versions of business cycles are considered. Basic clauses of the theory of the crises, which have been formed by the beginning of the XXI century, are specified. В статье исследуется генезис возникновения и развития кризисных явлений в экономиках стран мира и их исследований в работах ученых. Рассмотрены основные теории, объясняющие причины циклических кризисов и хронология изменения взглядов ученых на цикличность в развитии социально-экономических систем. Определена сущность понятий «кризис» и «экономический кризис». Рассмотрены функции кризиса в динамике развития систем и стадии кризиса. Поскольку кризис является одной из стадий экономического цикла, рассмотрены фазы такого цикла в экономике и основные разновидности экономических циклов. Выделены положения теории кризисов, сформировавшиеся на начало XXІ в.